Investigation of Knowledge of Using Medicinal Plants of the Dao Ethnic Group in Phan Thanh Commune, Cao Bang Province - Hoang Phuong, Ngo; Thien Kim, Le; Van On, Tran; Duc Trong, Nghiem (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
This study, "Investigation of knowledge of using medicinal plants of the Dao ethnic group in Phan Thanh commune, Cao Bang province", was undertaken to systematically document the traditional ethnobotanical knowledge regarding the use of medicinal plants by the Dao community in Phan Thanh commune. The results obtained 202 species of medicinal plants belonging to 83 families, 166 genera and 07 life forms. In addition, 30 diseases/uses were recorded using medicinal plants to treat and 18 remedies. Regarding the conservation status, the results indicate that 05 species are officially listed under Vietnam’s Decree No. 84/2021/ND-CP, 03 species are included in the Vietnam Red Book, and 29 species are recognized in the National List of Essential Medicines. The findings underscore the substantial potential value of the medicinal plant resources within Phan Thanh commune for sustainable exploitation and the establishment of dedicated cultivation areas. Key species identified as having significant potential include Disporopsis longifolia Craib, Ampelopsis cantoniensis (Hook.et.Arn) Planch and Sarcandra glabra (Thumb.) Nakai.